Fresh Azolla, Azolla pinnata as a Complementary Feed for Oreochromis niloticus: Growth, Digestive Enzymes, Intestinal Morphology, Physiological Responses, and Flesh Quality - Mohamed M. Refaey; Ahmed I. Mehrim; Osama A. Zenhom; Hamada A. Areda; Janice A. Ragaza; Mohamed S. Hassaan (Aquaculture Nutrition)
Azolla is a potential fish feed ingredient due to its high nutritional value, abundant production, and low price. This study is aimed at evaluating the use of fresh green azolla (FGA) as a replacement ratio of the daily feed intake on the growth, digestive enzymes, hematobiochemical indices, antioxidant response, intestinal histology, body composition, and flesh quality of monosex Nile tilapia, Oreochromis niloticus (with an average initial weight of 108.0±5.0 g). Five experimental groups were used and differed in commercial feed replacement rates of 0% (T0), 10% (T1), 20% (T2), 30% (T3), and 40% (T4) with FGA for 70 days. Results showed that 20% replacement with azolla gave the highest values of growth performance and hematological parameters and the best feed conversion ratio, protein efficiency ratio, and fish whole body protein content. The highest levels of intestinal chymotrypsin, trypsin, lipase, and amylase were noted in 20% replacement with azolla. Fish fed diets with FGA levels of 10% and 40% showed the highest values for the thickness of the mucosa and submucosa layers among all treatments, respectively, while the length and width of the villi decreased significantly. No significant (P>0.05) differences in the activities of serum alanine transaminase, aspartate transaminase, and creatinine were detected among treatments. The hepatic total antioxidant capacity and the activities of catalase and superoxide dismutase significantly (P<0.05) increased while the activity of malonaldehyde decreased with increasing the replacement levels of FGA up to 20%. With increasing levels of dietary replacement with FGA, muscular pH, stored loss (%), and frozen leakage rate (%) were significantly decreased. Finally, it was concluded that the dietary replacement of 20% FGA or less may be considered a promising feeding protocol for monosex Nile tilapia, which may lead to high fish growth, quality, profitability, and sustainability for the tilapia production sector.